Chilaiditi’s sign and syndrome: theoretical facts and a case report - Zvezdin, Biljana S; Savić, Nevena; Hromiš, Sanja; Kolarov, Violeta; Taušan, Djordje; Krnjajić, Bojana (Vojnosanitetski pregled, 2016)
Introduction. Chilaiditi’s syndrome is a rare condition manifested by gastrointestinal symptoms, and radiologically verified by transposition of the large intestine loop. This radiological finding with no manifested symptoms is termed the Chilaiditi’s sign. The aim of this case report was to remind the clinicians of the possibility of this rare syndrome, whose symptoms and signs may be misinterpreted and inadequately treated, with consequent diverse complications. Case report. We presented the theoretical facts and a patient in whom the diagnosis of Chilaiditi’s syndrome was established incidentally, when hospitalized for an exacerbation of his chronic obstructive pulmonary disease. The Chilaiditi’s sign was verified as an incidental finding on chest X-ray performed to evaluate the primary disease. Conclusion. Chilaiditi’s syndrome is a benign condition which rarely requires surgery. Its clinical importance lies in adequate differential diagnostic approach and timely management of potentially serious complications.